Pengaruh Kepuasan Kerja Terhadap Kinerja Karyawan Melalui Komitmen Organisasi Sebagai Variabel Intervening Pada Pt. Jambi Ekspres Televisi - Selviana Zandroto; Sumarni Sumarni; Rts. Ratnawati (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research aims to determine the effect of job satisfaction on employee performance with organizational commitment as an intervening variable at PT. Jambi Express Television. The analytical method used is quantitative descriptive analysis. The population and research sample consisted of employees of PT. Jambi Ekspres Television with a total sample of 30 people. Data collection was carried out by distributing questionnaires using a Likert scale. The statistical analysis used is the Structural Equation Modeling (SEM) technique with Partial Least Square (PLS) as an analysis tool, using the SmartPLS program. The research results show that job satisfaction has a positive and significant influence on employee performance, job satisfaction also has a positive and significant influence on organizational commitment, and organizational commitment has a positive and significant influence on employee performance. Apart from that, job satisfaction has a positive and significant effect on employee performance which is mediated by organizational commitment. Thus, it can be concluded that organizational commitment functions as a link between job satisfaction and employee performance. Employees who feel satisfied tend to be more enthusiastic and work harder, so that their performance increases and has a positive impact. This also increases their commitment to the company, helping to achieve company goals.